Golf historical aspects for development - Pavliuk, Iryna (My University, 2019)
Today, golf is the most expensive, prestigious and respectable sport. Sports game in the fresh air passing through stunning lands capes. At the same time, golf, which has passed the centuries-old way of development, has become one of the most popular types of sports.
Keywords: гольф; спорт; golf; sport; кафедра фізичного виховання